2018
DOI: 10.31235/osf.io/af8qk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increases in Sex with Same-Sex Partners Across U.S. Cohorts Born 1920-1998: A Race-Gender Intersection

Abstract: We examine change across U.S. cohorts born between 1920 and 1998 in their probability of having had sex with same-sex partners last year and since age 18. We explore how trends differ by gender, race and class background. We use data from the 1988-2016 General Social Surveys. We find steady increases across birth cohorts in the proportion of men and women who have had both male and female sexual partners since age 18. A key finding is a race-gender intersection: black men and women of all races had similar inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The estimates for those who identify as gay or bisexual are slightly larger here compared to the proportion of people who identify as gay or bisexual in Britain and Australia (see Geary et al 2018;Ritchers et al 2014); however, this is to be expected with a younger sample, as NSFG only sampled Americans aged 15-45 while Britain sampled adults aged 16-74 and Australia sampled adults aged 16-69. Indeed, many studies show that younger individuals are more likely to identify as non-heterosexual compared to older individuals (see Bridges and Moore 2018;England et al 2016;Mishel et al 2018a). Table 1 also shows that there are many gender differences when assessing how men and women age 15-45 label their sexual orientation: significantly more women than men identify as bisexual, and significantly more men than women identify as gay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimates for those who identify as gay or bisexual are slightly larger here compared to the proportion of people who identify as gay or bisexual in Britain and Australia (see Geary et al 2018;Ritchers et al 2014); however, this is to be expected with a younger sample, as NSFG only sampled Americans aged 15-45 while Britain sampled adults aged 16-74 and Australia sampled adults aged 16-69. Indeed, many studies show that younger individuals are more likely to identify as non-heterosexual compared to older individuals (see Bridges and Moore 2018;England et al 2016;Mishel et al 2018a). Table 1 also shows that there are many gender differences when assessing how men and women age 15-45 label their sexual orientation: significantly more women than men identify as bisexual, and significantly more men than women identify as gay.…”
Section: Resultsmentioning
confidence: 99%
“…And, it suggests that women are more sexually fluid in terms of same-sex sex and same-sex attraction compared to men. England et al (2016) and Mishel et al (2018a) argue that there is more same-sex sex among women than men due to the asymmetry of the gender revolution. Specifically, they argue that the gender revolution sent the message that gender nonconformity was more acceptable than before; and, given that deviations from exclusive heterosexuality are seen as gender nonconforming, part of the implicit message was permission to have same-sex sex.…”
Section: Intersections Between Sexual Identity Sexual Attraction Anmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these findings, studies show that women are generally more sexually fluid than men in terms of engaging in same-sex sexual behavior. Both large, survey-based quantitative studies and qualitative studies using smaller samples show that more women report having same-sex sex and same-sex attraction than men (e.g., Diamond 2008Diamond , 2014England et al 2016;Gates 2011;Laumann et al 1994;Mishel et al 2018;Mishel n.d.). Research has also shown that same-sex sexual behavior is sometimes strategically mobilized by heterosexual-identifying women who seek to garner attention from men (e.g., Hamilton 2007).…”
Section: Policing Sexual Orientation and The "One-act Rule"mentioning
confidence: 99%